Design of Web-Based Incoming and Outgoing Mail Information System at Diskominfo Kabupaten Tapanuli Tengah - Roni Syahputra Nduru; Candra Mecca Sufyana (Jurnal Info Sains : Informatika dan Sains, 2023)
The use of technology that has developed in the current era plays an important role in assisting an activity in the field of information systems. The Communication and Informatics Office in the Central Tapanuli district is a government agency that manages incoming and outgoing mail to communicate with organizations inside and outside the agency. fulfilled, such as minimal information received. A web-based information system is needed to be able to solve problems in managing mail. Researchers created an information system for incoming and outgoing mail to improve the quality and efficiency of mail management using the Waterfall method in a series of development processes that used UML (Unified Modeling Language) using the programming language PHP, Python, HTML and Mysql database. It is expected that with this information system it is hoped that it will become a proposed system to facilitate the management of letters quickly and accurately.